"Why do medical students fail in studies?" A case study - Foong, Chan Choong; Holder, Nurul Atira Khairul Anhar; Nik Nazri, Nik Nadia; Hong, Wei-Han; Pallath, Vinod; Sim, Joong Hiong; Vadivelu, Jamuna (2017)
Revealing reasons as to why medical students struggle in their studies would help to develop corresponding student support for students. As early remedial actions could prevent further attrition and dropouts, the purpose of this study is to investigate possible reasons for medical students failing their Year 1 studies.